PENGARUH PENGGUNAAN TEKNIK AKROSTIK TERHADAP KETERAMPILAN MENULIS PUISI SISWA KELAS IV SD MUHAMMADIYAH 10 TALLO KOTA MAKASSAR - Nurhilda, Nurhilda; Sulfasyah, Sulfasyah; Karumpa, Aco (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine how the application of acrostic techniques impacts the ability of students to write poetry in grade IV of Muhammadiyah 10 Tallo Elementary School, Makassar City. This study uses a quantitative approach, using a pre-experimental type and a one-group pretest-posttest design. Sampling in this study used total sampling, where 24 students as the population in Grade IV, there were 4 students who did not participate in all research activities (pretest, posttest and treatment). So they were not included in the analysis, so the number of samples analyzed was 20 students. The instruments used were observation sheets and test sheets (pretest and posttest). Data analysis techniques used were descriptive and inferential statistical analysis as well as normality and hypothesis tests (t-test). The results showed that students' poetry writing skills were significantly influenced by the use of acrostic techniques; the average pretest score of 44.85 increased to 82.15 in the posttest, and the normality test showed that the data were normally distributed (p <0.05). Therefore, this method can be used successfully to improve the ability of grade IV elementary school students in writing poetry.